Treatment of glioblastoma in adults - Wolfgang Wick; Matthias Osswald; Antje Wick; Frank Winkler (Therapeutic Advances in Neurological Disorders, 2018)
The diagnosis of a glioblastoma is mainly made on the basis of their microscopic appearance with the additional determination of epigenetic as well as mutational analyses as deemed appropriate and taken into account in different centers. How far the recent discovery of tumor networks will stimulate novel treatments is a subject of intensive research. A tissue diagnosis is the mainstay. Regardless of age, patients should undergo a maximal safe resection. Magnetic resonance imaging is the surrogate parameter of choice for follow up. Patients should receive chemoradiotherapy with temozolomide with the radiation schedule adapted to performance status, age and tumor location. The use of temozolomide may be reconsidered according to methylguanine DNA methyltransferase (MGMT) promoter methylation status; patients with an active promoter may be subjected to a trial or further molecular work-up in order to potentially replace temozolomide; patients with an inactive (hypermethylated) MGMT promoter may be counseled for the co-treatment with the methylating and alkylating compound lomustine in addition to temozolomide. Tumor-treating fields are an additive option independent of the MGMT status. Determination of recurrence is still challenging. Patients with clinical or radiographic confirmed progression should be counseled for a second surgical intervention, that is, to reach another macroscopic removal of the tumor bulk or to obtain tissue for an updated molecular analysis. Immune therapeutic approaches may be dependent on tumor types and molecular signatures. In newly diagnosed and recurrent glioblastoma, bevacizumab prolongs progression-free survival without affecting overall survival in an unselected population of glioblastoma patients. Whether or not selection can be made on the basis of molecular or imaging parameters remains to be determined. Some patients may benefit from a second radiotherapy. In our view, the near future will provide support for translating the amazing progress in understanding the molecular background of glioblastoma in to more complex, but promising therapy concepts